GENOTYPIC AND MODIFICATIONAL VARIABILITY OF THE PASSIVE DEFENSE RESPONSE TO HUMANS IN DOMESTIC PIGS - V. S. Lankin (Вавиловский журнал генетики и селекции)
A comparative study of the role of feeding motivation in the phenotypic expression and variation of the passive response to humans in specialized crossbred pigs: Laconi, paternal line, and unique sino-european Tiameslan, maternal one, was carried out. It was found that the genotype-feeding motivation interaction represented a factor of environmental variation of this behavior inseparable from ethological tests. The contribution of the interaction averages 60 % of total phenotypic variation of defensive behavior in pigs of both lines. An integrated approach is proposed to minimize modification variability in such adaptive behavior. It adequately describes its genotypic diversity in farm animals.